Use of the hyrax device in a patient with extra number included: Case report (Research, Society and Development, 2023)
Introduction: Hyperdontia is a numerical irregularity determined by the existence of additional teeth in the arch. Most cases occur in the maxilla, and can be classified into: conical or pin-shaped, tubercular and supplementary. Thus, the objective of this study is to present a clinical case report of a child with palate atresia and an impacted supernumerary tooth who received treatment with the Hyrax expander. Case report: A 9-year-old female patient, melanoderma, sought dental care together with her parents at the specialization clinic in Pediatric Dentistry of the Brazilian Association of Dental Surgeons - section PI with the main complaint of the absence of a maxillary central incisor. Thus, the placement of the Hyrax orthopedic device was programmed, for the expansion of the arch and to promote the spontaneous displacement of the supernumerary in order to facilitate the posterior extraction of the supernumerary. Once the device was placed, there was subsequent clinical and radiographic follow-up of the displacement. The prognosis for supernumerary tooth extraction and eruption of the impacted tooth without orthodontic traction is favorable due to non-closure of the root apex. Final considerations: The proper diagnosis, with the completion of a therapeutic plan consistent with each case, enables intervention in a timely manner to stop complications in the permanent dentition.